2011
DOI: 10.1517/13543776.2011.587959
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Akt with small molecules and biologics: historical perspective and current status of the patent landscape

Abstract: Introduction Akt plays a pivotal role in cell survival and proliferation through a number of downstream effectors; unregulated activation of the PI3K/PTEN/Akt pathway is a prominent feature of many human cancers. Akt is considered an attractive target for cancer therapy by the inhibition of Akt alone or in combination with standard cancer chemotherapeutics. Both preclinical animal studies and clinical trials in humans have validated Akt as an important target of cancer drug discovery. Area covered A historic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(37 citation statements)
references
References 126 publications
(156 reference statements)
0
36
0
Order By: Relevance
“…Akt is critically involved in multiple signaling cascades, controlling cell growth and proliferation, and its activation is a prominent feature of many human cancers. On the basis of the strong rationale for targeting Akt for cancer therapy, multiple attempts to identify Akt inhibitors with acceptable pharmaceutical properties have been pursued (17). However, despite the significant progress in identifying Akt small-molecule inhibitors, selectivity has been a key issue for many previously reported ATP-competitive Akt inhibitors (relative to the kinome, especially within the AGC kinase family), raising concerns on safety and unclear mechanisms of action of these drugs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Akt is critically involved in multiple signaling cascades, controlling cell growth and proliferation, and its activation is a prominent feature of many human cancers. On the basis of the strong rationale for targeting Akt for cancer therapy, multiple attempts to identify Akt inhibitors with acceptable pharmaceutical properties have been pursued (17). However, despite the significant progress in identifying Akt small-molecule inhibitors, selectivity has been a key issue for many previously reported ATP-competitive Akt inhibitors (relative to the kinome, especially within the AGC kinase family), raising concerns on safety and unclear mechanisms of action of these drugs.…”
Section: Discussionmentioning
confidence: 99%
“…The 3 isoforms of Akt have both overlapping and distinct functions and expression profiles (16,17). Activation of all 3 Akt family members have been detected in a variety of human malignancies, and inducible short hairpin RNA (shRNA) knockdown studies suggest that inhibition of all 3 Akt isoforms is required for maximum efficacy in PTENdeficient cancer xenograft models (18).…”
Section: Introductionmentioning
confidence: 99%
“…Inhibitors targeting the PI3K-AKT pathway members, including AKT, are currently in various stages of development (36,37). Previous studies have shown that AKT allosteric inhibitors require an intact PH-KD interface, because such inhibitors preferentially bind the closed PH-in conformation (16,17,38).…”
Section: Discussionmentioning
confidence: 99%
“…Several ATP-competitive and allosteric smallmolecule inhibitors of AKT are in development and/or clinical trials (36,37). Previous studies have shown that allosteric AKT inhibitors require an intact PH-KD interface for their activity (17,(38)(39)(40).…”
Section: Disruption Of Akt2 and Akt3 Ph-kd Interactions Leads To Theirmentioning
confidence: 99%
“…The most common approaches described to date have been through the development of compounds that are either ATP-competitive or that prevent the formation of the active enzyme. 103 A number of Akt inhibitors are currently being tested in clinical trials, including allosteric inhibitors of inactive Akt. [104][105][106] CCT128930 (Compound 30) is a potent ATPcompetitive AKT inhibitor discovered using fragment and structure-based approaches.…”
Section: Compound 28mentioning
confidence: 99%